MODELLING THE STRUCTURAL PARAMETERS OF THE GLUE COMPOSITION AND STUDYING ITS ADHESIVE STRENGTH - Zolotov, S.; Pustovoitova, O.; Kamchatna, S.; Savisko, S.; Lytvynova, H. (Municipal economy of cities. Series: «Economy science», 2024)
The study considers a model of a filled polymer system to analyse the interaction and relationship between its components and adhesive properties. A two-phase system occurs in the filler composition, which forms a layer at the interface with properties different from the bulk properties of the filler and the binder. The system consists of a filler, a boundary layer, and a binder, with their properties accounted for with the accuracy of the manufacturing conditions and the dimensions of the sample. We found that the filler grains shape significantly affects the properties of the system, such as bond strength and water resistance. Distance analysis between filler particles showed that a decrease in its volume fraction in the composition leads to an increased distance between them. We can draw the most objective conclusions after processing the filler particles since, in this case, everything depends on the change of interactions at the boundary (the properties of the matrix in the volume practically do not change). In other cases (for example, in the case of changing the temperature and time conditions of preparation and testing), not only the surface but also the volume properties of the matrix change, and, accordingly, it is usually impossible to conclude the role of adhesion. Its processes are part of the adhesion strength of the adhesive material, so the adhesion strength (also called interfacial strength, boundary strength, and bond strength) has been the subject of constant research for several decades. Adhesion strength is a quantitative indicator of adhesion, i.e., a quantitative indicator of the adhesion forces between the polymer matrix and the dispersed filler as a substrate. While the wetting angle of the edge characterises the process of formation of an adhesive bond, the strength of adhesion characterises the process of its destruction. Knowing the limits of the ‘ideal’ adhesion region can answer the question of what limits to aim for to improve adhesion, but this requires practical measurement of the interfacial strength between the acrylic composition and the filler, which is challenging. As a result, the strength of the composite can be a monotonically increasing function of the adhesion strength, but only in a limited range of values. An increase in adhesion can lead to a decrease in the strength of the adhesive material, depending on the size of the filler particles and the volume fraction of the filler. Adhesion strength is a quantitative indicator of the adhesion strength between the polymer matrix and the dispersed filler. The strength of adhesion affects the strength of the composite material. The ideal adhesion strength depends on the size and volume fraction of the filler. Excessive adhesion strength can lead to a decrease in the strength of the adhesive material.